PENERAPAN EPISTEMOLOGI KE DALAM KAJIAN EKONOMI ISLAM: Telaah Pemikiran Muhammad Baqir Al-Shadr - Khoirul Fathoni (IJoIS: Indonesian Journal of Islamic Studies, 2020)
This article discusses the thoughts of Muhammad Baqir Al-Shadr on how to apply epistemology to the study of Islamic economics. Muhammad Baqir al-Shadr emphasized the importance of logic and the need for causality, the role of philosophical thought and theology in strong Islamic economic thought to combat these forces. The forces of neolebarism and capitalism. In this case Muhammad Baqir al-Sadr carried out a reconceptualization of the Islamic economic doctrine by involving a philosophical paradigm in the framework of his analysis. In this study using descriptive analytical methods and at the end of the study it can be understood that Islam is different from capitalism and Marxism. The starting point or first level in the Islamic economic system is distribution, not production as is the traditional political economy system. In the Islamic economic system, distribution of the resources of production precedes the production process, and any organization associated with the automated production process is at the second level.